The Role of WHO in Increasing Mental Health Awareness in South Korea in 2016-2019 - KURNIAWAN, Muhammad Okva Virandika; JUNED, Mansur (PT Keberlanjutan Strategis Indonesia, 2024)
Mental health is one of the main concerns for the World Health Organization (WHO). In 2012, the WHO announced that the most common mental health disorder affecting the global community is depression and the disease is a top priority to be treated globally in the context of mental health. South Korea is one of the UN member countries with a high death rate due to suicide due to depression. Although the prevalence of depression in South Korea has been reported to be much lower than in other countries, it is undeniable that every time South Korea is mentioned, the words